Performance Simulation and Optimization of Cylindrical Mirror-Spliced Parabolic Trough Solar Collector - Bowen Liu; Vian Mbabazi; Weidong Huang (Applied Sciences)
This paper proposes a new type of solar trough collector with a spliced cylindrical mirror and develops a new ray-tracing method to predict and optimize its performance. The mirrors of this system are composed of multiple cylindrical mirrors whose centers are on a parabola, and the normal vector of the centers of each cylindrical mirror is consistent with the normal vector of the parabola point where it is located. The new ray-tracing method is based on the transverse distribution of solar radiation, and it has been validated with Soltrace, with the maximum intercept factor error in the calculations being less than 0.31%. This paper compares the spliced cylindrical mirror trough solar system with the conventional parabolic trough system and finds that the influence of cylindrical, spherical, and coma aberration can be reduced to negligible levels by adjusting the system design. At the same time, the slope error and cost of the cylindrical mirror are much less than the parabolic mirror so it has better performance from numerical simulation. The spliced cylindrical mirror system can be further optimized to achieve an annual net efficiency of 65.52% in the north–south horizontal axis tracking mode.